2018
DOI: 10.18280/mmc_c.790310
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing anaerobic digestion of wheat straw through multistage milling

Abstract: The effects of a mechanical pretreatment, carried out by a two stages mill followed by fractionation into two different products, were determined on the biodegradability and methane yield of wheat straw. Straw was chopped in a knife mill to an average length of about 30 mm, and a portion was used as reference material. Pretreatment reduced the size of the processed straw, whose median particle size was 300μm and 1200μm for the fine and the coarse fractions, respectively. Untreated and pretreated materials were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The table shows that there is no particular particle size of lignocellulose materials that is applicable for the optimum biogas yield of all the available feedstock. It can be observed that when the particle size of water hyacinth was reduced from 1.0 to 0.05 mm, the yield increased from 10 to 16% [ 107 ], whereas when wheat straw particle size was reduced from 1.2 to 0.3 mm, there was a decrease of 19.1 mL/g VS in the biogas yield [ 108 ]. It can also be inferred that at 0.3 mm particle size, different biomass produced different result.…”
Section: Optimization Of Biogas and Methane Yieldsmentioning
confidence: 99%
See 2 more Smart Citations
“…The table shows that there is no particular particle size of lignocellulose materials that is applicable for the optimum biogas yield of all the available feedstock. It can be observed that when the particle size of water hyacinth was reduced from 1.0 to 0.05 mm, the yield increased from 10 to 16% [ 107 ], whereas when wheat straw particle size was reduced from 1.2 to 0.3 mm, there was a decrease of 19.1 mL/g VS in the biogas yield [ 108 ]. It can also be inferred that at 0.3 mm particle size, different biomass produced different result.…”
Section: Optimization Of Biogas and Methane Yieldsmentioning
confidence: 99%
“…It can also be inferred that at 0.3 mm particle size, different biomass produced different result. There was an increase of 4.6 mL/g Vs when rice straw was pretreated to 0.3 mm particle size [ 109 ], while the biogas yield was increased by 77.8 mL/g VS when wheat straw was pretreated to the same 0.3 mm particle size [ 108 ]. Likewise, it was shown that different mechanical pretreatment methods also have different effects on the same lignocellulose biomass.…”
Section: Optimization Of Biogas and Methane Yieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, barley straw presented an increase of 54% and 41% of methane yield at particle size of 5 mm and 20 mm, respectively [73]. It can also be observed that particle sizes larger and smaller than the range between 2 and 5 mm, presented a decrease in methane yield [68,73,74]. The observed variations on the effect of particle size, time, and speed of milling pointed out that apparently the best strategy for the mechanical pretreatment depends on the type the lignocellulosic material and a universal strategy cannot be recommended.…”
Section: Mechanicalmentioning
confidence: 99%
“…Chemical pretreatment technique in terms of acid, alkali, oxidation and ozonolysis pretreatments has been reported to be a very effective technique for biogas/biomethane yield enhancement (Appels et al, 2011;Zhang et al, 2011;Biswas et al, 2014;Cesaro and Belgiorno, 2014;Ahring et al, 2015;Venturin et al, 2018;Antonopoulou et al, 2020;Dasgupta and Chandel, 2020;Lee et al, 2020). Physical pretreatment technique with respect to mechanical (milling), thermal (temperature-induced, steam explosion, liquid hot water), microwave irradiation, sonication and high-pressure homogenizer pretreatments have also been observed and reported to be moderately effective in the increase of biogas/biomethane yield (Hjorth et al, 2011;Pilarski et al, 2016;Dell'Omo and Froscia, 2018;Pengyu et al, 2017;M¨onch-Tegeder et al, 2014;Marañón et al, 2012;Bougrier et al, 2006;Ariunbaatar et al, 2014;Schwede et al, Frontiers in Energy Research frontiersin.org 13 2013;Menardo et al, 2012;Horn et al, 2011;Li et al, 2016;Lizasoain et al, 2017;Mulat et al, 2018;Steinbach et al, 2019;Weber et al, 2020;Passos and Ferrer, 2015;Qiao et al, 2013;Jiang et al, 2012;Panigrahi et al, 2019;Shang et al, 2019;Carrerre et al, 2016;Martin et al, 2013;Carrère et al, 2010;Ma et al, 2011). Table…”
Section: Effectiveness In Biogas/biomethane Enhancementmentioning
confidence: 99%